1988
DOI: 10.2527/jas1988.66198x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Growth and Estradiol Influence on Luteal Function in Mares

Abstract: Follicular growth, circulating estradiol concentrations and endometrial prostaglandin F2 alpha (PGF2 alpha) production were measured to determine whether there is an interrelationship among these factors associated with luteolysis. Follicular growth was monitored by rectal palpation every other day during diestrus in 16 mares. Plasma estradiol was determined for daily samples during all estrous cycles. Endometrial tissue was removed for PGF2 alpha analysis by radioimmunoassay on d 10, 12, 14 or 16 during sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…The divergence in E2 concentrations between the groups beginning on Day 16 represented increasing concentration in the IOI group but not in the PCL group, consistent with a report that E2 did not increase during the late diestrus in mares with PCL [26]. These findings for E2 apply to mares in which PCL has already been established and thereby represent the consequences of persistent P4 concentration rather than for a role of E2 as an etiologic factor.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The divergence in E2 concentrations between the groups beginning on Day 16 represented increasing concentration in the IOI group but not in the PCL group, consistent with a report that E2 did not increase during the late diestrus in mares with PCL [26]. These findings for E2 apply to mares in which PCL has already been established and thereby represent the consequences of persistent P4 concentration rather than for a role of E2 as an etiologic factor.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, divergence in LH between the groups began within a day after the reported diameter of the largest follicle at deviation (22-25 mm; [47,55]). In a previous study, follicle emergence was delayed in mares that developed spontaneous PCL [26]. In contrast, a negative effect on follicles in the present study was indicated by a slower growth of the largest follicle but not by a delay in day of emergence.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations